Pengaruh Motivasi dan Disiplin Belajar terhadap Prestasi Matematika Siswa Kelas V SD Muhammadiyah 4 Kandangsapi Jebres Surakarta Tahun 2015/2016 - Wardhani, Relaxia Mayliana Metty Kusuma, Drs. Saring Marsudi, SH. M.Pd (2016)
The purpose of this research was to determine: (1) the influence of motivation towards mathematics achivement, (2) the influence of learning discipline towards mathematics achivement, and (3) the influence of motivation and learning discipline towards mathematics achivement of fifth grader in SD Muhammadiyah 4 Kandangsapi. This type of research is a quantitative research in the form of a survey. The population are 32 students of fifth grade in SD Muhammadiyah 4 Kandangsapi. The main data collecting techniques used questionnaires and documents, supporting technique were interview. Instruments tested with validity and reability test. The data proccessing used multiple linear regression analysis and correlation of product moment by SPSS version 16. The results showed that (1) there is influence of motivation towards mathematics achievement with a value tcount = 2,576 > ttable = 2,042 and a significance 0,015 < 0,05, (2) there is influence of learning discipline towards mathematics achievement with a value tcount= 2,058 > ttable = 2,042 and a significance 0,049 < 0,05, and (3) there are influence of motivation and learning discipline towards mathematics achievement of fifth grader in SD Muhammadiyah 4 Kandangsapi with a value Fcount = 40,599 > Ftable = 3,33 and a significance 0,00 < 0,05. Keywords: Motivation, learning discipline and mathematics achievement.